ANALISIS TINGKAT KELELAHAN KERJA BERDASARKAN BEBAN KERJA FISIK PERAWAT DI INSTALASI RAWAT INAP RSU HAJI SURABAYA - Rizky Maharja (The Indonesian Journal of Occupational Safety and Health, 2015)
ABSTRACTNurses are working with high expectation, especially nurses at inpatient care unit are. They are to always be ready to  provide health treatment to the patients for 24 hours for 7 days. This high expectation may affect and inflicting fatigue on them. Work fatigue is a condition of activity, motivation and physical exhaustion. If nurses don’t take a rest, it can accumulated work fatigue eventually drops the health condition of the nurse off. This research aims to analyze level of work fatigue based on physical workload of the nurses in Inpatient Care Unit of RSU Haji Surabaya. This observational descriptive study applied cross-sectional study design. The research was conducted nurses at ward IIIC and IVC. The respondents are 27 nurses with following the criteria of this. The research applied Kruskal Wallis test to find out the variety of the work fatigue level based on physical workload and Spearman correlation test to find out the relationship between physical workload and work fatigue. The result showed that several characteristics of most of the respondents were aged between 30 and 49 years old, female, had been working for more than 5 years, married, normal nutritional status, and low calorie intake. The result also showed the average workload and the nurses might experience moderate work fatigue. The result of inter-variables correlations indicated there were correlation between physical workloads and work fatigueand there are varieties of the work fatigue based on the physical workload.Keywords: nurse, physical workload, work fatigue